WHERE THERES SMOKE: PROBLEMS & POLICIES CONCERNING SMOKING IN THE WORKPLAC (Tufts Archival Research Center, 2007)
Missing Page(s); Report by the Bureau of National Affairs (BNA) entitled “Where there’s Smoke: Problems and Policies concerning smoking in the workplace.” Emphasizes that smoking in the workplace is "under attack." States that measures have been taken in the past five years to minimize the presence of smoking in the workplace. Cites claims and counter claims for the elimination of employee smoking in public workplaces. Describes how the issue of smoking has come into the spotlight over the last decade and has had detrimental effects on tobacco companies.